What comes first, origin or production method? An investigation into the relative importance of different attributes in the demand for eggs - Lopez-Galan, B.; Gracia, A.; Barreiro-Hurle, J. (Spanish Journal of Agricultural Research, 2013)
This paper analyses consumer preferences for different eggs attributes to assess the importance placed by consumers on the origin and method of production when shopping. The data comes from an experiment conducted in Spain during 2009. An Error Component Random Parameter Logit model is used to estimate the effect of different eggs characteristics on consumers’ utility and derive their willingness to pay. Results suggest that consumers positively value the free-range and organic method of production and the local and regional origin and that they are willing to pay an additional € 0.85 for each package of six free-range or organic eggs, € 0.77 for locally produced and € 0.27 for regional produced eggs. Hence, the least valued eggs for consumers are those produced in cages and outside the region. Relative to this product, the highest willingness to pay corresponds to free-range or organic eggs followed by locally produced eggs and finally, by the regional eggs. Thus, we can conclude that Spanish consumers give more importance when shopping for eggs to the method of production than to the origin of production.